STUDI POLA ASUH ORANG TUA PADA ERA MODERN DI KOTA TARAKAN - Siti Fatimah; Urotul Aliyah (Jurnal Bimbingan dan Konseling Borneo, 2019)
The purpose of this research to find out how parents do parenting in the modern era of tarakan city.  The method of the research used in the study is a qualitative method by using design case study. The subject in this study consists of three parents in the modern era.  As of the subject matter of the research process was snowball sampling. The method of data collection was observation and interviews. The result showed that (1) Cendana’s family is incline to the democratic parenting, it can be showed when the child asks something, the parents are, consider first the good and back side, the parents pay attention about  the hearty, the education, and the child’s religion problem (2) Cemara’s family is incline to the authoritative parenting, it can be showed to each parents’ wishes should be do, the child is afraid and the effect rare to cry. Meanwhile the parents still pay attention the health of child. But to the education and religion, the parents incline neglectful parenting. The parents feel when the child in institute, the child is not beeded the guidance at home. The parents feel when they give the complee facilities, the duty of the parents are done (3) cempaka’s family is incline to the authoritative parenting, it can be shower when the child make a mistake, the parents divectly give the punishument. Neanwhile the parents still the child’s health, but in education and religion the parents is incline to negiectful parenting. The parents think handover to institute intentional becaous the parents do not have so much time for the child and the parents give the complete facilities for making happy their child.   The key words: parenting, parents, modern era.